Comparative evaluation of antioxidant activities and chemical composition of selected Schizophyllum commune Fr. natural, gamma-irradiated and hybrid strains / Alyaa Abbas Fadhil Alkhafaji - Alyaa Abbas , Fadhil Alkhafaji (2021)
Due to the uncontrolled production of reactive oxygen species, excessive level of free radicals leads to oxidative stress which is linked to many diseases such as cancers, diabetes, neurological disorder and hypertension. The major countermeasure to balance the excessive presence of free radicals in the body is to obtain substantial amounts of dietary antioxidants. Mushrooms contain many bioactive compounds with health-promoting effects including antioxidants. Therefore, this study was designed to investigate the antioxidants activities and chemical compositions of different strains of Schizophyllum commune Fr. The crude extracts of the natural (isolated from Malaysia and Thailand), gamma-irradiated (strains obtained when natural strains subjected to different doses of gamma radiation) and hybrid (strains obtained from hybridisation between the natural strains) strains of S. commune were prepared using 80% (v/v) aqueous ethanol. The antioxidant activities of the extracts were then measured using 2,2 diphynel-1-picrylhydrazyl radical scavenging activity (DPPH), 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) (ABTS), ferric reducing antioxidant power (FRAP) and cupric ion-reducing antioxidant capacity (CUPRAC) assays, and correlated to their chemical compositions. S. commune strains showed moderate total phenolic content (11.7-22.8 mg GAE/g extract) and high protein content (293.5-486.8 mg protein/g extract). The crude extracts of S. commune strains showed comparable scavenging activities in both DPPH radicals scavenging activities ranged from 2.30 to 2.48 (mmol TE/g extract) and ABTS radicals scavenging activities ranged from 0.07 to 0.15 (mmol TE/g extract). In FRAP (0.22 to 0.30 mmol Fe2+/g extract) and CUPRAC (0.10 to 0.13 mmol TE/g extract) assays, the crude extracts showed comparable reducing activities. The antioxidant activities of the crude extracts showed moderate correlation with the total phenolic (r = 0.625) and flavonoid (r = 0.535) content. Further investigation was on the liquid-liquid fractionation of the crude extracts of the strains W, W2000 and W4000 to yield the hexane, ethyl acetate and water fractions. For all selected strains, the water fractions contained the highest sugar, protein and phenolic content while the hexane fractions gave the highest flavonoid content. The ethyl acetate fractions of all selected strains also showed stronger antioxidant activities approximately one time higher than water fractions and two times higher than hexane fractions in all antioxidant assays. These findings suggest that the antioxidant compounds in the crude aqueous ethanol extracts of S.commune were successfully concentrated in the ethyl acetate fractions and the strongradical scavenging and reducing activities of the fractions might be attributed to the abundance both phenolics and flavonoids based on the correlation studies. Our findings have shown that S. commune strains and ethyl acetate fractions of the selected strains (W, W2000 and W4000) are a good source of natural antioxidants and hence, they will be potentially useful for medicinal and food applications.